RANCANG BANGUN SISTEM PENGUKURAN SUHU DAN KELEMBABAN UDARA MENGGUNAKAN SENSOR SHT75 BERBASIS INTERNET OF THINGS DENGAN DISPLAY SMARTPHONE - Iqbal, Muhammad; Yulkifli, Yulkifli; Darvina, Yenni (BERKALA FISIKA, 2019)
Temperature and humidity are important weather parameters for large purposes, such as agriculture, aviation, tourism, etc. The Indonesia's Meteorology, Climatology and Geophysics Agency is converting from conventional measuring instruments into digital systems. This research aims to determine the performance and design specifications of the internet of things for measuring the air temperature and humidity using the SHT75 sensor with a smartphone display. The system was built from SHT75 module sensor as temperature and humidity sensors with NodeMCU ESP8266 microcontrollers that can access the internet network so that data can be sent to the ThingSpeak. Data server from ThingSpeak appeared on smartphones using AppInventor. The instrument builder circuit was in a 5x5x10 cm3 box containing the SHT75 sensor,the NodeMCU ESP8266, the ON/OFF switch, the RESET button, and the adapter to connect to the source. It was found that results of the design specifications of the measuring instrument has a high accuracy and precision. The accuracy of measuring instruments for air temperature is 98.89% and for air humidity is 99.41%. The precision of measuring instruments for airtemperature and humidity are 99.73% and 99.08%, respectively.Keyword : SHT75, NodeMCU ESP8266, Internet of Things, ThingSpeak, App Inventor